From folk therapy to evidence-based psychiatry practice: The benefit of evidence-based psychiatry in treatment-naive psychotic patients. (September 2020) - Wang, Hung-Yu; Huang, Joh-Jong; Su, Shu-Fang; Hsu, Sheng-Hao; Chou, Li-Shiu; Chou, Frank Huang-Chih
Background: As Taiwan's Mental Health Act (MHA) clearly states that the human rights and legal rights of psychotic patients should be respected and guaranteed; however, a temple asylum violates the law in the 21st century. Hundreds of patients were constrained in the asylum for years without consent. Because of outbreak of infectious diseases, patients were evacuated from the asylum by the official intervention. Aims: To evaluate the outcomes of these patients from folk therapy to conventional treatment. Method: The study recruited the drug-naive psychotic patients constrained in an asylum for decades. Before and after the formal treatment, 253 patients were diagnosed with schizophrenia and other psychotic disorders with assessment of using the Mini Positive and Negative Syndrome Scale (Mini-PANSS) and Comprehensive Occupational Therapy Evaluation (COTE) scale. In addition, family function, self-care ability and nutritional status were also evaluated. Results: The initial data show the improvement in psychotic symptoms and occupational function in these patients. Furthermore, the ratio of patients who were classified as being at risk for malnutrition was decreased by 21.7% after treatment. There was no statistically significant difference in self-care ability before and after treatment. Conclusion: The psychotic symptoms and occupational function of these patients were improved after the formal treatment compared to the folk therapy. The care model for the psychotic patients in the temple asylum should be more thoroughly discussed in consideration of the medical ethics principles.